Risk of increased expression of ACE2 membrane protein in patients with hypertension: Review of COVID-19 - Pooladi, Mehdi; Hushmandi, Kiavash; Entezari, Maliheh (Archives of Advances in Biosciences, 2021)
Context: In late 2019, COVID-19 launched a pandemic from around Wuhan, China. It`s called the SARS-CoV-2 virus which belongs to the corona family and it has a lot in common with SARS-CoV-2, but it has been reported to be more common. Evidence Acquisition: The risk of the virus is high for people with high blood pressure and use medication. The reason for this potential and risk for COVID-19 is an increase in expression in a membrane protein called ACE2. This protein is responsible for converting Ang I to Ang1-9 as well as converting Ang II to Ang1-7. Results: Its pathogenic role is due to its receptor for SARS-CoV-2 and SARS-CoV. Research has shown that there is a significant link between hypertension, Increase the expression and activity of ACE2 and having coronavirus. That`s why our goal is to remind people of high blood pressure about the risk of developing Covid-19. We studied ACE2 and Covid-19 from a clinical and biological point of view. In the following we have shown the position and the type of virus connection to ACE2 with the help of protein database. Conclusion: In the SARS-Cov-2, there are four structural proteins and several non-structural proteins together with capsid can contain positive-stranded RNA viruses. Studies have shown that the Spike (S) protein binds strongly to the chain E and F with the ACE2 receptor.